Heteroepitaxial α-Ga2O3 MOSFETs with a 2.3 kV breakdown voltage grown by halide vapor-phase epitaxy. (1st July 2022) - Jeong, Yeong Je; Park, Ji-Hyeon; Yeom, Min Jae; Kang, Inho; Yang, Jeong Yong; Kim, Hyeong-Yun; Jeon, Dae-Woo; Yoo, Geonwook
Abstract: Here, we report on heteroepitaxial α -Ga2 O3 MOSFETs with a breakdown voltage (BV) of 2.3 kV at a specific on-resistance of 335 mΩ cm 2 . High-quality α -Ga2 O3 layers were grown on a sapphire substrate via halide vapor-phase epitaxy (HVPE). A stack of Ti/Al/Ni/Au was used for the S/D electrode, exhibiting significantly reduced contact resistance as compared with a conventional Ti/Au stack. Consequently, the record BV and mobility of 20.4 cm 2 V −1 s −1 were achieved. Moreover, a consistent critical field of 1 MV cm −1 was obtained for variable LGD . Our results are superior to recently reported heteroepitaxial α -/ β -Ga2 O3 MOSFETs, which is promising toward HVPE α -Ga2 O3 based power devices.